Authority Reformulation of Gender Equal Marriage Guardians: 4 Jurisprudence Schools Law of Marriage Guardians - Nada, Qathrun; Fajriyah, Iklilah Muzayyanah Dini (Interdisciplinary Social Studies, 2023)
Backgrounds: The existence of a guardian in the marriage contract within the framework of Islamic law in Indonesia is a condition that must be met by the bride. This means that the marriage contract is not valid if in the process there is no guardian accompanying the bride. The problem is that guardianship listed in the legal framework in Indonesia only gives full authority to fathers who are male. This is because the views of fiqh in Islamic marriage law in Indonesia take the Imam Syafi'i school of thought. Aim: The research would like to analyze the authority reformulation of gender equal marriage guardians through the lens of 4 jurisprudence schools. Methods: The article used the literature review method by utilizing secondary data from 3 Islamic yellow books and other supporting ones like journals and books. Findings: This study shows that the four schools of fiqh indicate the existence of opportunities or potential for female heads of households to become marriage guardians for their daughters.